Low energy availability, menstrual dysfunction, and impaired bone health: A survey of elite para athletes - Brook, E. M.; Tenforde, A. S.; Broad, E. M.; Matzkin, E. G.; Yang, H. Y.; Collins, J. E.; Blauwet, C. A. (Scandinavian Journal of Medicine & Science in Sports, 2019)
The Female Athlete Triad (Triad) is a syndrome describing three interrelated conditions: low energy availability (LEA), menstrual dysfunction, and low bone mineral density (BMD). Relative Energy Deficiency in Sport (RED-S) expands the Triad to include multiple physiologic consequences of LEA in both sexes. The purpose of this study is to determine the prevalence of factors associated with the Triad/RED-S in an elite para athlete population. Methods: Athletes were U.S. elite para athletes training to qualify for the 2016 or the 2018 Paralympic Games. Participants completed an online questionnaire characterizing nutrition, menstrual status (in females), bone health, and awareness of the Triad/RED-S. Results: The athletes were 260 elite para athletes (150 male, 110 female). While few reported prior eating disorder (3.1%), 32.4% had elevated Eating Disorder Examination Questionnaire (EDE-Q) pathologic behavior subscale scores. Most athletes (95 male, 65 female) were attempting to change their body composition or weight to improve performance. Forty-four percent of premenopausal females had oligomenorrhea/amenorrhea. Bone stress injury was reported in 9.2% of athletes; of these, 54.5% (n = 12) had low BMD. Less than 10% of athletes reported awareness of the Triad/RED-S. Conclusions: Factors associated with the Triad/RED-S are present in an elite para athlete population, regardless of sex or sport type. Awareness of the Triad/RED-S in para athletes is low. The consequences of LEA in para athlete populations are poorly understood. However, the high prevalence of factors observed suggests value in advancing screening tools and education efforts to optimize health in this population.